Diagnosa Penyakit Bakterial Pada Ikan Nila (Oreocrhomis niloticus) Yang Di Budi Daya Pada Jaring Tancap Di Danau Tondano - Ashari, Chairanitansyah; Tumbol, Reiny A; Kolopita, Magdalena E.F (e-Journal BUDIDAYA PERAIRAN, 2014)
This research aimed to diagnose bacterial diseases on nile tilapia cultured in stick net cage in Lake Tondano. Fish samples were taken from three locations of net cages in Lake Tondano namely Paleloan, Eris and Remboken villages. Three samples of fish were taken from each location/village. The samples taken showed clinical symptoms of bacterial infection such as hemorrhagic on the abdomen, the base of the fin, anal and chest, irregular swimming fish, hemorrhagic on the gills, fish refuse food, remain silent on the outskirts of net cage. Bacteria were isolated by using a sterile loop from head kidney (anterior kidney), which is located on the front, below the spine near the head. Bacterial cultures were performed on TSA media by making a zigzag scratches. The petri dish containing bacterial isolates were subsequently incubated in an incubator at a temperature of 35oC for 24 hours. The water quality parameter data measured consisted of temperature, Dissolved Oxygen, pH, ammonia, brightness. The results of the study showed that farmed tilapia in Lake Tondano has been infected with Aeromonas hydrophila that causes MAS (Motile Aeromonad Septicemia). The water quality, both chemical and physics around the net cages in the Lake Tondano was still in good condition and suitable for fish cultivation. Â  Keywords: Oreocrhomis niloticus, Bacterial disease, septicemia aeromonad motile, fixed net cage, Lake Tondano